Mobile application: gamification in NILAM reading program for schools / Muhammad Nur Aiman Ahmad Mokhtaza - Ahmad Mokhtaza, Muhammad Nur Aiman (2022)
Nowadays the development in mobile application is rapidly increasing due to the age of technology. Everyone owns a smartphone at least. This is an opportunity as a developer to create an application for smartphone. This is a documentation of a project titled, Mobile Application: Gamification in NILAM Reading Program for Schools. This project is divided into five chapter: Chapter 1: Introduction, Chapter 2: Literature Review and Chapter 3: Methodology, Chapter 4: Project Design and Implementation and Chapter 5: Conclusion and Recommendation.